Factors influencing the decision to travel in the Old Town of Takua Pa, Takua Pa District, Phang Nga Province (Journal of Pharmaceutical Negative Results, 2023)
The objectives of this study were to 1) study the motivation of tourists to travel in the Old Town of Takua Pa, Takua Pa District, Phang Nga Province 2) study the factors influencing tourism decisions in the Old Town of Takua Pa, Takua Pa District, Phang Nga Province. The population used in the study was tourists visiting the Old Town of Takua Pa 400 people using questionnaires as a tool to collect information. Analyze the data by finding percentages and averages.The results showed that  1) the motivation of tourists to tour Takua Pa Old Town, Takua Pa District, Phang Nga Province; Push Factors There is a high level of influence (   = 3.68).When separated by factors, it was found that the need factor to increase knowledge or study culture had a high degree of influence (  = 4.17), followed by the need to fulfill one's needs. (   = 4.02) The need to find novelty. (  = 3.66) the urge for relaxation and the desire to flee. There is a high level of influence (  = 3.63) and the need for travel, adventure, excitement, or entertainment. The influence was moderate ( = 2.91) in each case. In terms of pull factors, there is a very high level of overall opinion(  = 3.73). It shows that tourists pay attention to the descending tourism attraction factors in the following order: the cost of living or expenses (   = 4.22) The person living in the locality or culture has a large level of influence (  = 3.92)  terrain or location (   = 3.88) the facilities (  = 3.92) tourism resources have a large level of opinion (  = 3.75) there is a large level of influence, respectively, and the agencies, organizations, public and private policies of tourism in Thailand. Moderate reviews (  = 2.70)2) Factors influencing tourism decisions in Takua Pa Old Town, Takua Pa District, Phang Nga Province include: 7P's business marketing mix factors Because once separated into aspects, there is a high level of influence, with the price side of the product, the service (   = 4.16), the service process (   = 4.12), the service product (  = 4.11), the physical environment (   = 4.09), the staff (   = 3.93), the distribution of services, (   = 3.81) and the promotion of marketing (   = 3.61), respectively.